Flexure behaviour of foamed concrete incorporating BSP and POFA strengthened with CFRP - Aziz, Khalidah; Mohamad, Noridah; Tahir Lakhiar, Muhammad; A. A. Samad, A.; Jusoh, Suriani; Sofia, Anis (International Journal of Engineering and Technology, 2019)
This paper investigated the flexural behavior of lightweight foamed concrete (LFC) incorporating banana skin powder (BSP) and palm oil fuel ash (POFA), strengthened with carbon fiber reinforce polymer (CFRP) plate. The BSP and POFA are added in the LFC mixture at various percentages as cement and sand replacement, respectively. LFC cubes incorporating BSP and POFA, LFC-BSP-POFA, were cast and tested under compression to determine its compressive strength. LFC-BSP-POFA prisms strengthened with 100 mm and 150 mm length of CFRP plates glued on its bottom mid-span surface were cast and tested under four point bending load to determine its flexure behaviour. From the results obtained, compressive and flexural strength increased when percentages of BSP and POFA incorporated in the LFC increased. Meanwhile, CFRP plate managed to strengthen the LFC prism further where higher ultimate load recorded when longer CFRP plate was used.Â
Keywords: Lightweight Foamed Concrete; Agricultural Waste; Compressive Strength; Ultimate Flexure Load; Crack Pattern.